2022
DOI: 10.1111/aor.14189
|View full text |Cite
|
Sign up to set email alerts
|

A computational framework for post‐TAVR cardiac conduction abnormality (CCA) risk assessment in patient‐specific anatomy

Abstract: Background Cardiac conduction abnormality (CCA)‐ one of the major persistent complications associated with transcatheter aortic valve replacement (TAVR) may lead to permanent pacemaker implantation. Localized stresses exerted by the device frame on the membranous septum (MS) which lies between the aortic annulus and the bundle of His, may disturb the cardiac conduction and cause the resultant CCA. We hypothesize that the area‐weighted average maximum principal logarithmic strain (AMPLS) in the MS region can pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The anonymized patient’s CT scan was acquired at Stony Brook University Hospital under the approval of the local institutional review board. The patient model, shown in Figure 2 a, was reconstructed following the procedures described in our previous study [39]. Briefly, the pre-TAVR CT scan of the selected patient was imported as DICOM file and segmented into 3D surface meshes using ITK-SNAP 3.6 [40].…”
Section: Methodsmentioning
confidence: 99%
“…The anonymized patient’s CT scan was acquired at Stony Brook University Hospital under the approval of the local institutional review board. The patient model, shown in Figure 2 a, was reconstructed following the procedures described in our previous study [39]. Briefly, the pre-TAVR CT scan of the selected patient was imported as DICOM file and segmented into 3D surface meshes using ITK-SNAP 3.6 [40].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, additional patient-specific computational modeling may provide more accurate predictions of patient specific CCA risk. Recently, computational studies on patient-specific structural models have indicated that elevated contact pressure and contact pressure index (CPI) on the His bundle region in the intraventricular septum below the triangular space between the RCL and NCL for self-expandable TAVR cases (Rocatello et al 2018) and high area-weighted average logarithmic strain (AMPLS) and Contact force for balloon expandable TAVR cases were associated with onset of CCA following TAVR procedure (Reza et al 2022). To gain more insight into the mechanisms underlying post-TAVR CCA development and provide a more accurate assessment of CCA risk, it is essential to analyze the interaction between the TAVR prosthesis and conduction fibers within a realistic, electromechanically coupled, beating heart condition.…”
Section: Introductionmentioning
confidence: 99%